Development of Distance Learning During the Pandemic Period Using the Android Application (e-Sabaky) in Physics Subjects at SMA Negeri 1 Pati - Sudargini, Yuli; Purwanto, Agus (International Journal of Social and Management Studies, 2021)
This study aims to develop a learning media for the development of open and distance learning. The learning media developed in the form of an Android-based application during the pandemic. This research method is the development method (RnD), which is developing a model of distance learning facilities and then applying it to the distance learning process during the pandemic. The location of this research is at SMA Negeri Pati then applied in several high schools outside Pati district such as Kudus and Rembang districts. The implementation period is from 2018 to 2020. Media E-SABAKY (Electronic Communicative Active Learning Application System Yuli) is effective and efficient for teaching concrete and fun materials for quantities and units for students which can be installed via student mobile phones. It can also be done cooperatively through SOM application collaboration group activities. Benefits of implementing E-SABAKY in learning Among them are for students to improve learning outcomes in terms of quantities and units. For teachers as a means to improve learning innovation and reference material to conduct similar research. For schools, as a consideration for the addition of supporting media for learning the material of quantity and unit, the results of daily tests will increase. E-SABAKY media is ecofriendly or environmentally friendly because it does not use paper. All learning materials to exams are all in the application. This learning system adapts to the needs of millennials which are identical to Android.